A Subtitling Analysis On Elysium MovieBy Sang Pangeran - Isnaini, Neti; , Dr. Dwi Haryanti ,M. Hum (2016)
SUMMARY NETI ISNAINI. A320120102. A SUBTITLING ANALYSIS ON ELYSIUM MOVIE BY SANG PANGERAN. Research Paper. School of Teacher Training and Education Muhammadiyah University of Surakarta. May, 2016. This research focuses on the subtitling analysis on Elysium movie by Sang Pangeran using Gottlieb theory about subtitling strategy. The objectives of this research are (1) to classify the subtitling strategies found in Elysium movie and its subtitle and (2) to identify the readability of the subtitling strategies found in Elysium movie and its subtitle. This type of this research is descriptive qualitative. The object of this research is the Elysium movie and its subtitle. The data are all utterance or sentences found in the Elysium movie written by Neill Blomkamp and its subtitle. The writer uses documentation and interviewing technique to collect the data. The writer uses triangulation to prove the validity of the research where the data sources are from movie and informant. The result of this research shows that the writer found 1215 data of Elysium movie containing of subtitling strategy. There are paraphrase strategy 13,25%, transfer strategy 36,5%, imitation strategy 9,46%, transcription strategy 1,31%, condensation strategy 1,8%, decimation strategy 0,32%, deletion strategy 35,8%, resignation strategy 1,56%. The readability of subtitling strategy is divided into high readability, medium readability and low readability. The subtitling of Elysium movie is readable. From 1215 data there are 1196 data has score 3 of readability or 98,4% and 19 data included to resignation strategy. The finding shows that the readability level of this data is high. From the subtitling strategies which used in the Elysium movie they are more data which categorized as high readability level. The high readability is more dominant in this subtitling. Keywords: Subtitling, strategy, readability